Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Desa Leppangeng Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Rahmawati, Sitti; Kumala Putri P, Andi Sri; Ayu, Ari (Paser Institute Of Accounting and Finance, 2024)
The aim of this research is to determine the effect of taxpayer awareness and tax sanctions on taxpayer compliance in paying land and building taxes in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency, both partially and simultaneously. The method used in this research uses quantitative research methods with a correlation research type. The data used in this research is primary data obtained from distributing questionnaires to 86 land and building tax payers in Leppangeng Village using a sampling technique. Simple Random Sampling, then the data obtained was processed using the SPSS program. The data analysis method used in this research is multiple linear regression analysis. The results of this research show that (1) partially taxpayer awareness has a positive and significant influence on taxpayer compliance in paying land and building taxes. (2) partially tax sanctions have a positive and significant influence on taxpayer compliance in paying land and building taxes. (3) simultaneously taxpayer awareness and tax sanctions have a positive and significant influence on taxpayer compliance in paying land and building taxes.